Solidão criadora: milonga e processos de subjetivação - Bohrer, Luiz Carlos Teixeira (2006)
This dissertation considers questioning the ways of experience the solitude preponderant currently, where they configure concepts as lack, melancholy and precariousness, allied to the romantic conception of subjectivity, conferring a negative status to the solitude. Making use of theoretical references of Deleuze, Guattari and Nietzsche, it points at other subjective forms of relating with the solitude, more unfastened forms of the understanding from a weakened human being, victimized. Thus, it deals with this subject as a territory multiple implications, being political, historical, etc., investigating critically. Furthermore, this investigation is articulated with a musical sort spread out in Rio Grande do Sul recognized as melancholic: milonga, that it has the solitude as frequent subject of its songs. Even being recognized of this form, milonga presents variations of perspective on the solitude, what it meets the proposal found in the theoretical references that it is used, serving like a production machine of a solitude wide open to the becoming since the experiences of self intensification